(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
Bryophytes are rich in a variety of secondary biological active compounds, thus provide a great potential for biotechnological and biopharmaceutical applications. Bryophytes contain potentially useful natural products, including polysaccharides terpenoids, lipids, amino acids and phenylpropanoids. Bryophytes isolated compounds and extracts have cytotoxic, antimicrobial activities. The result of our research indicate the presence in the extracts of bryophytes collected in Armenia, the entire spectrum of amino acids, especially essential ones. Also revealed in some species a certain amount of nitrogen – 840 mg/g, which indicates a more intensive synthesis of nonessential amino acids. The results obtained can be used in medicine, pharmacology.